Macular Bruch's membrane defects and axial length: association with gamma zone and delta zone in peripapillary region - Jonas, Jost B.; Ohno-Matsui, Kyoko; Spaide, Richard F.; Holbach, Leonard; Panda-Jonas, Songhomitra (Investigative Ophthalmology & Visual Science, 2013)
To examine histomorphometrically the macular region of highly myopic eyes.On horizontal anterior-posterior histological sections, we examined the posterior pole of 138 human globes (axial length: 20-35 mm). In the parapapillary region, we differentiated between the beta zone (Bruch's membrane without RPE), gamma zone (parapapillary region without Bruch's membrane), and delta zone (elongated and thinned gamma zone).In 12 (8.7%) eyes, a macular Bruch's membrane defect (MBMD) was detected. The MBMD showed a complete lack of RPE and choriocapillaris, and an almost complete lack of photoreceptors. Presence of MBMD was associated with longer axial length (P < 0.001), longer gamma zone (P = 0.04) and delta zone (P < 0.001), thinner peripapillary scleral flange, and thinner sclera just outside of the optic nerve meninges (P < 0.001) and at the posterior pole (P < 0.001). An MBMD was found only in eyes with an axial length of 27 mm or longer. MBMD prevalence in highly myopic eyes was 12/39 or 30.8%. MBMD presence was not significantly related to length of beta zone (P = 0.09). In multivariate binary regression analysis, MBMD presence was significantly (P < 0.001) associated only with axial length.Highly myopic eyes (axial length >=27mm) can show an MBMD associated with complete loss of RPE and choriocapillaris, and marked reduction of photoreceptors and large choroidal vessels. MBMD presence was strongly associated with axial length and indirectly with parapapillary gamma zone and delta zone. The myopia-associated secondary MBMDs may occur parallel to the myopia-associated widening of Bruch's membrane opening around the optic nerve head.
EVALuna2:21118